1999
DOI: 10.1075/sll.2.2.07ver
|View full text |Cite
|
Sign up to set email alerts
|

rood kool tien persoon in: Morfo-syntactische aspecten van gebarentaal [red cabbage ten person in: Morpho-syntactic Aspects of Sign Language(s)]

Abstract: The study reported on in this dissertation represents the first larger-scale research project on the grammar of Flemish-Belgian Sign Language. 1 Within the framework of the project a corpus consisting of six hours of spontaneous sign language data -four hours of dialogues and two hours of monologues -produced by ten (near)native signers, at the time of the research between 30 and 83 years old, was composed, transcribed and translated. The corpus served as a basis for the study of two different but related cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
2
1
Order By: Relevance
“…This tendency is noted so often that when a language does not exhibit it, the authors typically explicitly say that (as for Sign Language of the Netherlands, Coerts, 1994 ). Surprisingly, a study of Flemish Sign Language found more variation in word order in reversible sentences (where we find SOV and OSV) than in non-reversible (where we find only SOV) (Vermeerbergen, 1996 ). For the languages that favor SVO with plain verbs in reversible sentences, it would seem that NP 1 V NP 2 order is not ambiguous (interpreted only as SVO), whereas NP 1 NP 2 V order is open to the readings SOV and OSV (and see Fischer, 1975 ).…”
Section: Generalizations In the Datacontrasting
confidence: 65%
“…This tendency is noted so often that when a language does not exhibit it, the authors typically explicitly say that (as for Sign Language of the Netherlands, Coerts, 1994 ). Surprisingly, a study of Flemish Sign Language found more variation in word order in reversible sentences (where we find SOV and OSV) than in non-reversible (where we find only SOV) (Vermeerbergen, 1996 ). For the languages that favor SVO with plain verbs in reversible sentences, it would seem that NP 1 V NP 2 order is not ambiguous (interpreted only as SVO), whereas NP 1 NP 2 V order is open to the readings SOV and OSV (and see Fischer, 1975 ).…”
Section: Generalizations In the Datacontrasting
confidence: 65%
“…More specifically, SOV is predicted to be grammatical in all natural sign languages; however, “In reversible sentences with plain verbs 1 , SVO is favored” (Napoli & Sutton-Spence, 2014). Although our explanation for this pattern differs from theirs (which is based on ambiguity), the fact remains that these natural languages behave as our account predicts, with the only known counterexample being Flemish Sign Language, which permits both SOV and OSV for reversibles (Vermeerbergen, 1996; cited in Napoli & Sutton-Spencer, 2014). …”
Section: Discussioncontrasting
confidence: 53%
“…However, for sentences with non-reversible arguments no clear pattern stood out as SOV, SV and SVO were all found, indicating a large word order variation. Thus, Braes (2019) showed many similarities with the findings of Vermeerbergen (1996) and—however, based on fewer participants—carefully suggests that there is no distinct evolution or change in the word order of Flemish Sign Language.…”
Section: Research Using the Flemish Sign Language Corpusmentioning
confidence: 88%
“…In a similar vein, Braes (2019) echoed the work of Vermeerbergen (1996) to investigate word order and a possible evolution or change in VGT word order since the late 1990s. In the context of her bachelor’s thesis, she analyzed the Volterra declarative sentences ( Volterra et al, 1984 ), taken from the VGT Corpus, which were produced by 6 informants (3 male and 3 female, 19–25 years old).…”
Section: Research Using the Flemish Sign Language Corpusmentioning
confidence: 99%
See 1 more Smart Citation